Autotransplantation of spleen tissue in children with mansonic schistosomiasis who underwent splenectomy: Evaluation of splenic residual functions - Brandt,Carlos Teixeira (1998)
Autotransplantation of spleen tissue is an attempt for maintenance of splenic functions when splenectomy is indicated in children. It minimizes the risks of overwhelming postsplenectomy infection and it has been done in children with severe portal hypertension due to hepatosplenic mansonic schistosomiasis that underwent splenectomy. The purposes of this investigation were to study the morphology of the residual splenic tissue; to evaluate the residual filtration function of this splenosis; and to assess the immune response to polyvalent pneumococcal vaccine of these patients. Twenty-three children with portal hypertension from mansonic schistosomiasis who underwent splenectomy, ligature of the left gastric vein, autotransplantation of spleen tissue into an omental pouch were evaluated for residual splenic parenchyma and functions. Tc-99m sulfur colloid liver-spleen scans were used for detection of splenic nodules. The search for Howell Jolly bodies were used for assessing the filtration function and Enzyme-linked immunosorbent assay was used for measuring the relative rise in titter of specific pneumococcal antibodies. Splenosis was evident in all children; however, in two there were less than five splenic nodules in the greater omentum, which was considered insufficient. Howell-Jolly bodies were found in the peripheral blood only in these two patients with less evident splenosis. The immune response was adequate in 15 patients; it was intermediate in 4 patients and inadequate in 4 patients. Autotransplantation of spleen tissue into an omental pouch is efficient in maintaining the filtration splenic function in more than 90% of the cases and the immune response to pneumococcal vaccination in approximately 65% of the children.